Analisa Pembelajaran Aplikasi Bisnis Di Lazada - Etika Sabariah; Musthafa Kamil; Tri Indah Estiani; Dorit Hartini (CV. ITTC INDONESIA, 2024)
The internet provides great opportunities for business. Part of business expansion through the eCommerce platform provides learning to develop knowledge, especially for the Darul Hikmah Mosque DKM Management to increase their knowledge of Information Technology. Lazada is a marketplace founded and meeting between sellers and buyers in an economical method without meeting face to face. The facilities of this platform provide added value such as: free fees for opening an online stall/shop by Lazada. Payment and shipping methods have been integrated with this platform.